Diagnosis of sustainability in the furniture industry RS: A case study in factory in the Cai Valley - Naime, Roberto; Selbach, Eduardo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The paper is a case study in the furniture business in the Cai Valley, in Rio Grande do Sul, with a diagnosis of sustainability and containing survey information concerning industrial processes of the company. The field of engineering and product design, raw materials used, how the company uses its energy resources and its energy efficiency program will be among the issues discussed. There is also an investigation of the potential of optimizing the use of water resources, check the operation of wastewater treatment and solid waste and an investigation of how the company monitors air emissions. A survey of existence of community projects, there is transparency and social responsibility in business are also discussed in the work. Along with this study, are raised information regarding environmental sustainability projects in companies seeking to enable improved environmental issues with decreasing associated costs or economic return.